Efforts to Improve Learning Outcomes in Reviewing Novel Texts Through the SQ3R Method: Survey, Question, Read, Recite And Review of Class VIII F Students of Indonesian Language Learning at 7 Kediri Middle School - Ekowati, Priyastuti (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
Students of class VIII F of SMP 7 Kediri find it difficult with the many memorization and intentions of learning Indonesian. Students also do not pay too much attention to the explanation from the teacher when in class. Add to the Indonesian language lesson schedule at the end of the lesson. This makes the concentration of students declining and not the enthusiasm for learning. From the data obtained by the researchers, the average daily test scores of class VIII F students of Kediri Junior High School 7 only reached 74.4 or still below the determined KKM. The researcher chooses a learning method Survey, Question, Read, Recite and Review. The SQ3R method is an excellent reading method for intensive and rational reading purposes. The learning step for the SQ3R method is that the teacher asks students to observe or identify the entire text. Students are asked to arrange questions that are relevant to the text. The teacher guides students to find the main ideas and answers to the questions that have been made in the second step. Students mention, students review all questions and answers briefly. Teachers and students make conclusions together. The success of this study can be seen from the increase in student learning achievement up to 75% with a minimum KKM value of 78. The results of the increase can be seen from the data as follows: pre-cycle 53%; first cycle 69%; second cycle 81%. These results are said to be successful because they have exceeded the indicator of research success of 75%. The increase results can be seen from the average value of students as follows: pre-cycle 74.4; first cycle79,1; second cycle 82.2. These results are said to be successful because they have exceeded the indicator of success.